Digital technologies in the system of remote service - E. S. Belyaeva; P. V. Kovalenko; A. A. Sotnikov (Вестник Северо-Кавказского федерального университета)
Currently one of the main trends, which was largely influenced by the pandemic, is the digital transformation of all spheres of society. The financial sector is highly subject to digital modernization. In this area, both banking products and services that form the final consumer experience and affect their loyalty undergo digital modernization. Therefore, the introduction of digital technologies and digital transformation of business processes is currently a priority for banks. It contributes to their active expansion, reduces the costs, improves the quality and efficiency of banking services and customer loyalty and simplifies the mechanisms for providing services. The development of the banking system based on the use of digital technologies will solve many problems. For example, end-to-end technologies such as machine learning, artificial intelligence, blockchain, P2P lending, robo-advising accelerate technological changes, personalize offers, increase the speed of banking operations, increase the accuracy of calculations, and reduce the risk of deliberate misrepresentation of reporting data. This article defines the types of remote banking services, evaluates their use in Russian banks. Particular attention is paid to the influence of various factors on the development of remote banking services and the introduction of digital technologies, on the emergence of new functions in this area. It was revealed that as a result of the restrictions associated with COVID-19, banks immediately modified relations with customers and converted them to a digital basis.